Cognitive linguistics, second language acquisition, and foreign language teaching - Achard, Michel, 1959-; Niemeier, Susanne, 1960- (Studies on language acquisition, 2004)
This book shows that the notions developed within the Cognitive Linguistics movement afford an insightful perspective on several important areas of second language acquisition and pedagogy. The key concepts commonly invoked in cognitive analyses such as the usage-based conception of grammar, the radial organization of categories, metaphors, or cultural scripts, do not only represent powerful constructs within which the process of second language acquisition can be valuably investigated, but also allow teachers to successfully introduce problematic material in the foreign language classroom.